2015
DOI: 10.1016/j.ajo.2014.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Detachment Associated With AIDS-Related Cytomegalovirus Retinitis: Risk Factors in a Resource-Limited Setting

Abstract: Purpose To determine risk factors predictive of retinal detachment in patients with cytomegalovirus (CMV) retinitis in a setting with limited access to ophthalmic care. Design Case-control study. Methods Sixty-four patients with CMV retinitis and retinal detachment were identified from the Ocular Infectious Diseases and Retina Clinics at Chiang Mai University. Three control patients with CMV retinitis but no retinal detachment were selected for each case, matched by calendar date. The medical records of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Although in immunocompetent individuals HCMV infection is typically asymptomatic, in the case of congenital infection, the virus can cause severe neurological sequelae such as deafness and developmental defects following infection of the fetus (Grosse, Ross, and Dollard, 2008; Johnson and Anderson, 2014). In immunocompromised individuals, including those with HIV/AIDS or those receiving organ transplants, HCMV can cause devastating morbidity and mortality including pneumonia, retinitis, and transplant rejection (Ljungman, Hakki, and Boeckh, 2011; Paya et al, 2004; Yen et al, 2015). Moreover, many studies have shown that HCMV can be associated with chronic diseases such as atherosclerosis and hypertension, cancer, and autoimmune disease (Dziurzynski et al, 2012; Li et al, 2011; Streblow, Orloff, and Nelson, 2001; Varani et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although in immunocompetent individuals HCMV infection is typically asymptomatic, in the case of congenital infection, the virus can cause severe neurological sequelae such as deafness and developmental defects following infection of the fetus (Grosse, Ross, and Dollard, 2008; Johnson and Anderson, 2014). In immunocompromised individuals, including those with HIV/AIDS or those receiving organ transplants, HCMV can cause devastating morbidity and mortality including pneumonia, retinitis, and transplant rejection (Ljungman, Hakki, and Boeckh, 2011; Paya et al, 2004; Yen et al, 2015). Moreover, many studies have shown that HCMV can be associated with chronic diseases such as atherosclerosis and hypertension, cancer, and autoimmune disease (Dziurzynski et al, 2012; Li et al, 2011; Streblow, Orloff, and Nelson, 2001; Varani et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Among immunocompromised patients-especially those with an organ transplant, chemotherapy, or AIDS-the reactivation of virus causes life-threatening diseases, such as gastroenteritis, encephalitis, pneumonitis, and graft rejection (5)(6)(7). In addition, HCMV infection is also implicated in widespread ocular damage and potential vision loss from retinitis, anterior uveitis, and corneal endotheliitis (8)(9)(10)(11). Because HCMV infection of the iris is a risk factor during anterior uveitis, understanding the dynamics of viral infection at the molecular level becomes relevant for understanding the viral pathogenesis in general and developing novel strategies to prevent blindness.…”
mentioning
confidence: 99%
“…[14] A further study looked at risk factors for developing retinal detachments in patients with CMV retinitis and found bilateral disease and lesion size to be the strongest predictors. [15] Our study failed to demonstrate an association between the number of retinal quadrants involved and retinal detachment, but we did not specifically measure lesion size. Prophylactic argon retinal photocoagulation has been successful in anecdotal reports and small case series, [16] but there is no uniformity among the centres in SA with regard to treating patients prophylactically with laser.…”
Section: Discussionmentioning
confidence: 77%